Finite element model updating of semi-composite bridge decks using operational acceleration measurements. (1st November 2016) - Polanco, Néstor R.; May, Geoffrey; Hernandez, Eric M.
Graphical abstract: Highlights: Method uses acceleration measurements to identify composite action in bridge decks. The methodology was verified using various models of increasing complexity. The proposed method was validated using measurements from an operational bridge deck. In all cases examined the proposed methodology performed satisfactorily. Abstract: Composite bridge decks provide higher flexural moment capacity and stiffness compared to their non-composite counterparts. In order to achieve composite behavior, differential slip between the steel member and the concrete slab must be restrained by means of shear connectors. In older bridge decks composite behavior is uncertain. Uncertainty arises, among other things, due to lack of knowledge regarding the type of shear connector used (if any), cumulative damage due to fatigue, and aging effects. In this paper the authors propose the use of sensitivity-based finite element model updating to determine the degree of composite behavior of operational bridge decks with uncertain shear connectors. The free parameters of the models are: rigidity per unit length of the beam-slab interface and the elastic modulus of the concrete slab. The features used in the model updating procedure are the identified modal frequencies from operational acceleration measurements. A sequential sensitivity-based weighted least-squares solution was implemented. The proposed methodology is verified in various simulated bridge deck structures and validated in an operational and partially instrumented bridge deck with uncertain composite action.